Multi-Leg TiO(2)Nanotube Photoelectrodes Modified by Platinized Cyanographene with Enhanced Photoelectrochemical Performance - Shahrezaei, Mahdi; Hejazi, Seyyed Mohammad Hossein; Rambabu, Yalavarthi; Vavrecka, Miroslav; Bakandritsos, Aristides; Özkan, Selda; Zboril, Radek; Schmuki, Patrik; Naldoni, Alberto; Kment, Stepan (Catalysts, 2020)
Highly ordered multi-leg TiO(2)nanotubes (MLTNTs) functionalized with platinized cyanographene are proposed as a hybrid photoelectrode for enhanced photoelectrochemical water splitting. The platinized cyanographene and cyanographene/MLTNTs composite yielded photocurrent densities 1.66 and 1.25 times higher than those of the pristine MLTNTs nanotubes, respectively. Open circuit V(OC)decay (V-OCD), electrochemical impedance spectroscopy (EIS), and intensity-modulated photocurrent spectroscopy (IMPS) analyses were performed to study the recombination rate, charge transfer characteristics, and transfer time of photogenerated electrons, respectively. According to the V(OCD)and IMPS results, the addition of (platinized) cynographene decreased the recombination rate and the transfer time of photogenerated electrons by one order of magnitude. Furthermore, EIS results showed that the (platinized) cyanographene MLTNTs composite has the lowest charge transfer resistance and therefore the highest photoelectrochemical performance.
CRIS-Team WoS Importer:2020-08-14